Coady, Amanda. L to R Tom Coady, Lorretta Coady and Mandy Coady with a dog. - Heritage NL
Amanda Coady provided a picture of (from left to right) Tom Coady, Loretta Coady and Mandy Coady with a large dog. Tom and Loretta Coady both appear to be sitting. Tom Coady is smoking a cigarrette with his left hand and using his right hand to pet the dog on the neck. Mandy stands in the foreground of the image with her right hand on the dog's neck. Loretta Coady's head is visible between the heads of Tom and Mandy Coady. The dog is sitting and has their tongue hanging out of their mouth.